2018
DOI: 10.1002/jor.24101
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral resurfacing implantation angle is more important than implant material stiffness

Abstract: Osteochondral resurfacing implants are a promising treatment for focal cartilage defects. Several implant-factors may affect the clinical outcome of this treatment, such as the implant material stiffness and the accuracy of implant placement, known to be challenging. In general, softer implants are expected to be more accommodating for implant misalignment than stiffer implants, and motion is expected to increase effects from implant misalignment and stiffness. 3D finite element models of cartilage/cartilage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…However, according to a previous research, partial articular resurfacing surgery has a certain positive significance for joint function and local cartilage [ 15 ]. The mini-prosthesis relieves shear and friction forces around cartilages, thereby avoiding further cartilage damage [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to a previous research, partial articular resurfacing surgery has a certain positive significance for joint function and local cartilage [ 15 ]. The mini-prosthesis relieves shear and friction forces around cartilages, thereby avoiding further cartilage damage [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a previous research, partial articular resurfacing surgery has a certain positive significance for joint function and local cartilage [ 15 ]. The mini-prosthesis relieves shear and friction forces around cartilages, thereby avoiding further cartilage damage [ 15 ]. Some factors, including the hardness of the material, surface lubrication characteristics, biocompatibility of the material, and inflammatory properties of ions or small particles released by the material, have potential negative effects on cartilages and their microenvironment [ [15] , [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
“…Bionate® 75D (Sh) is the highest stiffness medical grade TPU and could potentially be used as a bone‐substitute (Geary, Birkinshaw, & Jones, 2008). An osteochondral implant fully composed of TPU has the potential to overcome the typical drawbacks of metal‐based implants, as it is MRI‐compatible and theoretically would not lead to excessive stress in opposing cartilage (Heuijerjans, Wilson, Ito, & van Donkelaar, 2018; Kanca et al, 2018). Polymers however, pose specific challenges when implanted in bone.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in an in vivo study, Martinez-Carranza et al, 2016 showed that damage to the opposing cartilage appears to be sensitive to implant position (Martinez-Carranza et al, 2016). Heuijerjans et al (2018) demonstrated using a computational approach, that softer materials such as PCU may be preferred when implant positioning is suboptimal. (Heuijerjans et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Heuijerjans et al (2018) demonstrated using a computational approach, that softer materials such as PCU may be preferred when implant positioning is suboptimal. (Heuijerjans et al, 2018). Another advantage of PCU implants over metal is that they can be imaged with MRI, the main orthopaedic imaging modality for cartilage defects.…”
Section: Discussionmentioning
confidence: 99%